Analisis Pola Narasi Reflektif Buku Teks Sejarah SMA Untuk Pencapaian Empati Sejarah - Heri Susanto; Hieronymus Purwanta (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2022)
The use of history textbooks is one of the keys to achieving the goals of historical education. Textbooks play an essential role in building students' historical empathy. A textbook present a reflective narrative that historical empathy. This study analyzes its narration in history textbooks has represented the aspect of historical empathy. The literature study method was used in this study. The object of research and data sources consist of 4 books from 3 publishers. Data analysis in this study was carried out by content analysis. The reliability used in this study is stability reliability, namely the reliability obtained by rereading the research data to understand the document. The results show that the books used by students had not fully the reflective narrative achieving historical empathy. There is no interrelation point of view. The textbook does not explore the thoughts. In addition, overall, books published by the Ministry of Education and Culture more reflective narratives that support the achievement of historical empathy compared to published by private publishers.